The Short Juozas Miltinis Manuscript Fund Inscriptions - Mikelinskaitė, Angelė (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English] The article presents an overview of the manuscript fund of director Juozas Miltinis’ (1907-1994) short inscriptions. Based on the small literary forms of the classification system, these short inscriptions are systematized and classified according to the recorded information purposes (theme) and content. Analyzing the short inscriptions of the fund, there is disclosed personal identity, historical period, social and cultural context in which they were noted and functioned.